Tissue factor regulation by miR-520g in primitive neuronal brain tumor cells: a possible link between oncomirs and the vascular tumor microenvironment - Asti, Esterina D'; Huang, Annie; Kool, Marcel; Meehan, Brian; Chan, Jennifer A.; Jabado, Nada; Korshunov, Andrey; Pfister, Stefan; Rak, Janusz (The American journal of pathology, 2016)
Pediatric embryonal brain tumors with multilayered rosettes demonstrate a unique oncogenic amplification of the chromosome 19 miRNA cluster, C19MC. Because oncogenic lesions often cause deregulation of vascular effectors, including procoagulant tissue factor (TF), this study explores whether there is a link between C19MC oncogenic miRNAs (oncomirs) and the coagulant properties of cancer cells, a question previously not studied. In a pediatric embryonal brain tumor tissue microarray, we observed an association between C19MC amplification and reduced fibrin content and TF expression, indicative of reduced procoagulant activity. In medulloblastoma cell lines (DAOY and UW228) engineered to express miR-520g, a biologically active constituent of the C19MC cluster, we observed reduced TF expression, procoagulant and TF signaling activities (responses to factor VIIa stimulation), and diminished TF emission as cargo of extracellular vesicles. Antimir and luciferase reporter assays revealed a specific and direct effect of miR-520g on the TF 3′ untranslated region. Although the endogenous MIR520G locus is methylated in differentiated cells, exposure of DAOY cells to 5-aza-2′-deoxycytidine or their growth as stem cell-like spheres up-regulated endogenous miR-520g with a coincident reduction in TF expression. We propose that the properties of tumors harboring oncomirs may include unique alterations of the vascular microenvironment, including deregulation of TF, with a possible impact on the biology, therapy, and hemostatic adverse effects of both disease progression and treatment.
Published online: December 11, 2015
Gesehen am 06.05.2016